Robust secure design for relay wireless sensor networks with simultaneous wireless information and power transfer - Hehao Niu; Bangning Zhang; Daoxing Guo; Mingyue Lu (International Journal of Distributed Sensor Networks)
In this article, we investigate the physical layer security problem in relay wireless sensor networks with simultaneous wireless information and power transfer. Specifically, by considering the energy receiver which may act as potential eavesdropper and assuming that only imperfect channel state information can be attained, we propose a joint robust beamforming and artificial noise scheme. We formulate the relay power minimization problem under both the secrecy rate constraint and the energy harvesting constraints, which is non-convex and hard to tackle. By studying the hidden convexity of the problem, we propose an iterative algorithm combining semi-definite relaxation and a gradient-based method. In addition, a suboptimal rank-one reconstruction method is presented. Simulation results show that the proposed robust scheme achieves better performance than other schemes.